Application of system archetypes in practice: an underutilised pathway to better managerial performance - Bureš, Vladimír; Racz, Fridrich (Journal of Business Economics and Management, 2016)
Current dynamic business environment forces managers to apply various tools in order to improve organisational performance and effectiveness. System archetypes enable to cope with complexity and make appropriate decisions. This study is theoretically grounded in the field of economic cybernetics and system archetype analysis. It applies qualitative research on the sample of 54 managers with the high level of seniority. The aim is to reveal whether system archetypes are effectively used in practice. Two hypotheses focused on both knowledge about and application of system archetypes are tested. The results prove that there are inconsistencies tied to forms of system archetypes insight and knowledge. Moreover, there is an inadequate level of attention identified in investigated organisations. Results imply various potential research pathways that are outlined in the final section of the paper. Hence, the manuscript offers a unique insight into the current state of practical system archetypes utilisation and contributes to the explanation of the role of system archetypes in the economic cybernetics framework.